Locating dayside magnetopause reconnection with exhaust ion distributions. Issue 5 (8th May 2017) - Broll, J. M.; Fuselier, S. A.; Trattner, K. J.
Abstract: Magnetic reconnection at Earth's dayside magnetopause is essential to magnetospheric dynamics. Determining where reconnection takes place is important to understanding the processes involved, and many questions about reconnection location remain unanswered. We present a method for locating the magnetic reconnection X line at Earth's dayside magnetopause under southward interplanetary magnetic field conditions using only ion velocity distribution measurements. Particle‐in‐cell simulations based on Cluster magnetopause crossings produce ion velocity distributions that we propagate through a model magnetosphere, allowing us to calculate the field‐aligned distance between an exhaust observation and its associated reconnection line. We demonstrate this procedure for two events and compare our results with those of the Maximum Magnetic Shear Model; we find good agreement with its results and show that when our method is applicable, it produces more precise locations than the Maximum Shear Model. Key Points: The location of dayside magnetopause reconnection is determined from reconnection exhaust ion velocity distributions Reconnection exhaust D‐shaped velocity distributions deform with increasing field‐aligned distance from their associated reconnection site The method is demonstrated with two Cluster magnetopause crossings; distances are consistent with Maximum Magnetic Shear Model calculations